Comparison of Milk Kefirs Obtained from Cow's, Ewe's and Goat's Milk: Antioxidant Role of Microbial-Derived Exopolysaccharides - Sana M'hir; Lamia Ayed; Ilaria De Pasquale; Elisabetta Fanizza; Ali Zein Alabiden Tlais; Roberto Comparelli; Michela Verni; Rosanna Latronico; Marco Gobbetti; Raffaella Di Cagno; Pasquale Filannino (MDPI AG, 2024)
Different types of milk are used in the production of milk kefir, but little information is available on the release of potentially antioxidant exopolysaccharides (EPS). The aim of this study was to investigate whether the microbial dynamics and EPS release are dependent on the milk substrate. In our study, the inoculated microbial consortium was driven differently by each type of milk (cow, ewe, and goat). This was evident in the sugar consumption, organic acid production, free amino release, and EPS production. The amount and the composition of the secreted EPS varied depending on the milk type, with implications for the structure and functional properties of the EPS. The low EPS yield in ewe's milk was associated with a higher lactic acid production and thus with the use of carbon sources oriented towards energy production. Depending on the milk used as substrate, the EPS showed different monosaccharide and FT-IR profiles, microstructures, and surface morphologies. These differences affected the antiradical properties and reducing power of the EPS. In particular, EPS extracted from cow's milk had a higher antioxidant activity than other milk types, and the antioxidant activity was concentration dependent.